2021
DOI: 10.1021/acs.joc.1c00494
|View full text |Cite
|
Sign up to set email alerts
|

The Regioselective Functionalization Reaction of Unprotected Carbazoles with Donor–Acceptor Cyclopropanes

Abstract: The regioselective functionalization reaction of unprotected carbazoles with donor–acceptor (D–A) cyclopropanes has been demonstrated for the first time. With Sc­(OTf)3 as Lewis acid catalyst, the N–H functionalization of carbazoles takes place through a highly selective nitrogen-initiated nucleophilic ring opening reaction. Significantly, by engaging TfOH as Brønsted acid catalyst, a straightforward C–H functionalization at the 3-position of the unprotected carbazole proceeds via Friedel–Crafts-type addition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…To introduce D–A functionalities onto the carbazole scaffolds, numerous synthetic approaches have been reported in the literature, which mainly include organometal-catalyzed reactions. Sekar et al have reported carbazole-derived D−π–A−π–D-based fluorophores via condensation of 2-[1-(9-ethyl-9 H -carbazol-3-yl)­ethylidene]­malononitrile with different aldehydes . Zhao et al have synthesized carbazoles containing D–A cyclopropanes by regioselective N–H/C–H functionalization of carbazole in the presence of TfOH or Sc­(OTf) 3 , but these procedures require either expensive metal catalysts or harsh reaction conditions. Herein, we have explored the simple chemistry of 2 H -pyranones for the synthesis of D–A-functionalized fluorescent carbazole derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…To introduce D–A functionalities onto the carbazole scaffolds, numerous synthetic approaches have been reported in the literature, which mainly include organometal-catalyzed reactions. Sekar et al have reported carbazole-derived D−π–A−π–D-based fluorophores via condensation of 2-[1-(9-ethyl-9 H -carbazol-3-yl)­ethylidene]­malononitrile with different aldehydes . Zhao et al have synthesized carbazoles containing D–A cyclopropanes by regioselective N–H/C–H functionalization of carbazole in the presence of TfOH or Sc­(OTf) 3 , but these procedures require either expensive metal catalysts or harsh reaction conditions. Herein, we have explored the simple chemistry of 2 H -pyranones for the synthesis of D–A-functionalized fluorescent carbazole derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…In the last 10–15 years, interest in the chemistry of donor–acceptor cyclopropanes (DACs) has grown sharply [ 1 , 2 , 3 , 4 , 5 ]. Their ring-opening transformations are widely used in organic synthesis to assemble various carbo- and heterocyclic compounds, including natural compounds and their analogs [ 6 , 7 , 8 , 9 , 10 ]. Currently, there are a variety of different types of DAC reactions being reported [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ring-opening reactions of DACs with carbon nucleophiles like indoles, 2-naphthols, electron-rich aromatic compounds, 1,3-dicarbonyl compounds, 6-aminouracils, ferrocene, and TMSCN have been well-established. Moreover, various heteroatom-nucleophiles such as phenols, water, alcohols, amines, azides, and purines as well as thiols have also been applied in the ring-opening processes for the construction of γ-heteroatom functionalized butyric acid derivatives. Ring-opening with sulfur nucleophiles has attracted our attention as it provides straightforward access to γ-thioether functionalized butyric acid derivatives, which could be applied to the construction of methionine analogues and other biologically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%